Perbandingan Penyerapan Anggaran APBD Sulawesi Selatan Sebelum Dan Masa Pendemi Covid-19 - Yadi Arodhiskara; Jumriani Jumriani; Fajar Ladung (Jurnal Akuntansi dan Keuangan Daerah, 2023)
Absorption of the budget is one of the stages of the budget cycle starting from budget planning, establishment and approval of the budget by the House of Representatives, in this case the study wanted to find out the comparison of the absorption of the South Sulawesi Regional Budget before and during the Covid-19 pandemic. The approach used in this research is a quantitative approach. The quantitative approach is a scientific inquiry based on logical positivism which operates with strict rules regarding logic, truth and prediction. The results of the Absorption of the Budget (measured by Regional Expenditure) research show that there is no statistically significant difference in budget absorption (measured by the Regional Revenue budget) for the last 6 years before and after the occurrence of Covid-19 in South Sulawesi Province. The results of the second study, namely Budget Absorption (measured by Regional Expenditure) statistically there is a significant difference in budget absorption (measured by Regional Expenditure) for the last 6 years before and after the occurrence of Covid-19 in South Sulawesi Province.